A clinical guide to inherited metabolic diseases - Clarke, Joe T. R. (Cambridge University Press, 2002)
This clinically organized, user-friendly, handbook is a guide to the recognition of inherited metabolic disease, and provides direction once diagnosis has been established. It is a well-illustrated text that presents biochemical and metabolic concepts in a clinically relevant context. The volume complements traditional textbooks which are organized biochemically, and serves as an entrance to the discipline, to help general physicians and advanced medical trainees to overcome the intimidation of dealing with metabolic problems. This new edition has been expanded to include substantially more information on mitochondrial diseases, new imaging techniques, and new techniques for screening and diagnosis